Dentum Karbala - Ade Maulana; Wimbrayardi Wimbrayardi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The musical composition Dentum Karbala is inspired by the Tabut ritual procession of the Bengkulu community, held annually from the 1st to the 10th of Muharram. This tradition is a form of mourning for the martyrdom of Prophet Muhammad’s grandson, Husain bin Ali bin Abi Thalib, in the tragedy of Karbala. The composer expresses the emotional outpouring of the Bengkulu people through each stage of the Tabut ritual, translated into musical form using local musical idioms such as the rhythmic patterns of Dol and harmonic exploration with Middle Eastern nuances. The creation method involves three stages: exploration, improvisation, and the formation of the final composition. The resulting work is structured into three main sections, each representing sadness, anger, and spiritual reverence. This composition emphasizes not only musicality but also serves as a medium to convey moral messages and the cultural values of the community. It is hoped that this work will inspire arts students to explore, create, and develop traditional arts in a contextual and creative manner.